The role of architectural engineering in macromolecular self-assemblies via non-covalent interactions: A molecular LEGO approach. (April 2020) - Su, Zebin; Zhang, Ruimeng; Yan, Xiao-Yun; Guo, Qing-Yun; Huang, Jiahao; Shan, Wenpeng; Liu, Yuchu; Liu, Tong; Huang, Mingjun; Cheng, Stephen Z.D.
Graphical abstract: Abstract: Macromolecular self-assembly has made explosive development in the last several decades, are being extensively explored in the fields of drug delivery, lithography, catalysis, molecular electronics, sensors, and so many others. In this review, we summarize the self-assembly of macromolecules such as polymers, dendrimers, molecular nanoparticles, colloids, DNA and proteins, from the aspect of architectural engineering and mainly focus on the periodic and quasi-periodic assembled structures. In particular, simple building blocks can be conjugated together to construct complex macromolecular motifs with different architectures and physical interactions. We first introduce the concept of architectural engineering, then present a brief overview of supramolecular interactions and five main categories of building blocks, including polymer coils, dendrons, rods, discs, and polyhedra. We further discuss the detailed self-assembly behaviors of fifteen types of specific macromolecular motifs involving different building blocks. Special attention is paid to the architectural effect of macromolecular self-assembly. In the end, future perspective on architectural engineering is briefly mentioned.